Enabling self-adaptive QoE/QoS control - Lima, Solange (2011)
Handling quality requirements of multimedia services and the expectations of end-users regarding the perceived service quality is currently a major issue for service providers in order to sustain service diversity and improve competitiveness. In this context, this paper presents ongoing work toward a service-oriented architecture for QoE/QoS evaluation and control, which can be deployed to assist the provision of multi-constrained services. Considering the users' QoE perspective and the negotiated service levels, the architecture lays on per service class online monitoring to assist self-adaptive control of multimedia flows entering the network. To perform online monitoring, a distributed and versatile QoS monitoring tool oriented to multiservice networks is proposed. Preliminary results shows that the presented control strategy is effective in providing consistent quality levels to heterogeneous services.